Six months of exercise programe twice a week seems to be not enought to improve cognitive function in older people - Diego Pastor Campos; Laura Carbonell Hernández; Eduardo Cervelló Gimeno (Asociación Española de Ciencias del Deporte, 2018)
Aging is a natural process that implies a physical and cognitive decline. In the last two decades, physical exercise has emerged as a powerful modulator of these processes, and an important lifestyle to reduce frailty and dependence. This study measure physical and cognitive performance of sixteen old people who participated in a six-month physical exercise program, twice a week. Our results show an improvement in strength and agility with the exercise program, and a tendency to improve cognitive outcomes depending of assistance. The variable assistance or maybe the exercise program leads to not find significant improvements in endurance, neither in cognitive responses, when all group is taken in care, and these two variables maybe are related.